2013
DOI: 10.1155/2013/523652
|View full text |Cite
|
Sign up to set email alerts
|

The Haptoglobin-CD163-Heme Oxygenase-1 Pathway for Hemoglobin Scavenging

Abstract: The haptoglobin- (Hp-) CD163-heme oxygenase-1 (HO-1) pathway is an efficient captor-receptor-enzyme system to circumvent the hemoglobin (Hb)/heme-induced toxicity during physiological and pathological hemolyses. In this pathway, Hb tightly binds to Hp leading to CD163-mediated uptake of the complex in macrophages followed by lysosomal Hp-Hb breakdown and HO-1-catalyzed conversion of heme into the metabolites carbon monoxide (CO), biliverdin, and iron. The plasma concentration of Hp is a limiting factor as evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
150
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(156 citation statements)
references
References 120 publications
2
150
0
4
Order By: Relevance
“…Lipocalin-2 and haptoglobin are involved in the regulation of iron metabolism, by binding small iron-carrying molecules (siderophores) and hemoglobin (before internalization by CD163 receptor), respectively. Iron capture protects against iron-mediated toxicity (40). This is in agreement with the described iron retention phenotype of M1 macrophages (41), which also has been described in early regenerating muscle (42).…”
Section: Discussionsupporting
confidence: 86%
“…Lipocalin-2 and haptoglobin are involved in the regulation of iron metabolism, by binding small iron-carrying molecules (siderophores) and hemoglobin (before internalization by CD163 receptor), respectively. Iron capture protects against iron-mediated toxicity (40). This is in agreement with the described iron retention phenotype of M1 macrophages (41), which also has been described in early regenerating muscle (42).…”
Section: Discussionsupporting
confidence: 86%
“…supported by many studies which demonstrated Hp elevation during bacterial infection, inflammation, tissue destruction, and various malignant diseases [3,32] and also consistent with Sritharanand et al [33] who reported high concentration of Hp in untreated LL patients as compared to healthy controls.…”
Section: Hp Concentrationsupporting
confidence: 82%
“…CD163 is a scavenger receptor that facilitates binding and endocytosis of hemoglobin‐haptoglobin complexes by monocytic cells, decreasing the cytotoxic load of free hemoglobin that occurs after tissue hemorrhage 10, 11. Recent evidence has shown that CD163 is also upregulated acutely in neurons following ICH both in vivo and in vitro 12.…”
Section: Introductionmentioning
confidence: 99%